Object-oriented programming in python - Goldwasser, Michael H., 1969- (Pearson Prentice Hall, 2008)
This book presents a balanced and flexible approach to the incorporation of object-oriented principles in introductory courses using Python. Familiarizes readers with the terminology of object-oriented programming, the concept of an object's underlying state information, and its menu of available behaviors. Includes an exclusive, easy-to-use custom graphics library that helps readers grasp both basic and more advanced concepts. Lays the groundwork for transition to other languages such as Java and C++. For those interested in learning more about object-oriented programming using Python.